Analisis Penerapan Zakat Pertanian pada LAZISNU Desa Kedungwangi Kecamatan Sambeng Kabupaten Lamongan - Rohman Machfud, Abdur; Ah. Subhan ZA, Moh. (Journal of Islamic Economics Studies and Practices, 2023)
Abstract: The purpose of this study was to determine the application of agricultural zakat and its realization by LAZISNU in Keduk Hamlet, Kedungwangi Village, Sambeng District, Lamongan Regency. This study uses a type of qualitative research and uses a descriptive analytical approach. Data collection techniques using observation, interviews, and documentation. The first result of this study is the application of zakat carried out by LAZISNU in Kedungwangi Village, namely the acquisition of rice farming zakat and the distribution of zakat that has been collected is distributed to mustahik who really need it with the results of deliberations by LAZISNU management, the deliberation is by way of listing the people who are entitled to receive from each RT and data information from the Kedungwangi Village government. The process of forming administrators from several hamlets in Kedungwangi Village should socialize the work program that will be carried out by prospective LAZISNU administrators.